Impact of Chest Radiation and Separate Coronary Ostia on Left Anterior Descending Artery Dissection in Female Patients - Shahzad, Azhar; Siddiqui, Fahad Irshaad; Hussain, Naveed; Imran, Haad; Nisar, Naheeda; Ali, Rizwan; Baig, Uzma (Indus Journal of Bioscience Research, 2025)
Background: Left anterior descending (LAD) artery dissection is a rare and potentially life-threatening condition, particularly in female patients with a history of chest radiation therapy and congenital coronary anomalies, such as separate ostia of the left coronary arteries. Objective: The main objective of the study is to find the impact of chest radiation and separate coronary ostia on left anterior descending artery dissection in female patients. Methodology: This retrospective observational study was conducted at Chaudhary Pervaiz Elahi Institute of Cardiology, Multan during January 2022 to January 2023. Data were collected from 22 female patients. Results: The mean age of patients was 58.4 ± 8.3 years, with a mean interval of 15.2 ± 6.7 years since chest radiation therapy. Hypertension (54.5%) and diabetes mellitus (40.9%) were common comorbidities. Chest pain was the predominant symptom (90.9%), and LAD dissection was confirmed in all cases through coronary angiography. Separate ostia of the left coronary arteries were identified in 100% of the cohort. Conservative management was applied in 59.1% of cases, while 31.8% underwent percutaneous coronary intervention (PCI), with 85.7% success. In-hospital mortality was 4.5%, and the 12-month event-free survival rate was 81.8%. Conclusions: It is concluded that LAD dissection in this population results from a combination of radiation-induced vascular damage and congenital coronary anomalies. Advanced imaging techniques are critical for diagnosis, and management should be personalized to patient stability and disease severity.